1987
DOI: 10.3133/ofr87677
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical well-log data base for the Gulf Coast aquifer systems, south-central United States

Abstract: As part of the U.S. Geological Survey's Regional Aquifer-System Analysis (RASA) program, the Gulf Coast RASA was begun to investigate groundwater flow systems in the Coastal Plain of the south-central United States. Three regional aquifer systems are identified in the area. The Mississippi embayment aquifer system and the Texas coastal uplands aquifer system are composed predominantly of Eocene sediments; the coastal lowlands aquifer system is composed predominantly of Oligocene and younger sediments. Automate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Progress on the study was reported by Grubb (1985, 1986b, 1987, 1992); Wilson and Hosman (1988) described a geophysical well-log data base; Weiss and Williamson (1985) presented a method for vertically subdividing thick sedimentary units; and maps, sections, and diagrams of the geohydrologic framework were constructed by Hosman (1982Hosman ( , 1988; Arthur and Taylor (1986); Mesko (1988Mesko ( , 1990; Parks and Carmichael (1989, 1990b, 1990c; Taylor and Arthur (1989);. Potentiometric surface maps were prepared for several aquifers, some for the first time, by Ackerman (1987aAckerman ( , 1987bAckerman ( , 1989b; Boswell and Arthur (1988); Garza and others (1987); Martin and Whiteman (1985a, 1985b; Martin and others andCarmichael (1990a, 1990b).…”
Section: Regional Analysis Of the Gulf Coast Aquifer Systemsmentioning
confidence: 95%
“…Progress on the study was reported by Grubb (1985, 1986b, 1987, 1992); Wilson and Hosman (1988) described a geophysical well-log data base; Weiss and Williamson (1985) presented a method for vertically subdividing thick sedimentary units; and maps, sections, and diagrams of the geohydrologic framework were constructed by Hosman (1982Hosman ( , 1988; Arthur and Taylor (1986); Mesko (1988Mesko ( , 1990; Parks and Carmichael (1989, 1990b, 1990c; Taylor and Arthur (1989);. Potentiometric surface maps were prepared for several aquifers, some for the first time, by Ackerman (1987aAckerman ( , 1987bAckerman ( , 1989b; Boswell and Arthur (1988); Garza and others (1987); Martin and Whiteman (1985a, 1985b; Martin and others andCarmichael (1990a, 1990b).…”
Section: Regional Analysis Of the Gulf Coast Aquifer Systemsmentioning
confidence: 95%
“…• The potentiometric surface raster, which was output from the interpolation process, was compared to a raster of the aquifer base (Saucier, 1994;Wilson and Hosman, 1987;Hart and others, 2008; James Hoffmann, Mississippi Department of Environmental Quality, written commun., February 2018; Joseph Richards, U.S. Geological Survey, written commun., March 2018; Wacaster and others, 2018) to identify where the input potentiometric surface raster was below the aquifer-base raster.…”
Section: Characterizing the 2016 Potentiometric Surface Raster And Comentioning
confidence: 99%
“…The hydraulic conductivity values for Permeable Zones C, D, and E are somewhat lower than Prudic's values. However, the majority of well tests on which Prudic [1991] based his analysis for Permeable Zones C-E were carried out in more permeable outcrop regions [Wilson and Hosman, 1988]. In calibrating their groundwater flow model of the Coastal Lowlands Aquifer System, Williamson and Grubb [2001] determined that the hydraulic conductivity of Zones C -E were much lower in southern Louisiana than in the north.…”
Section: Hydrogeologic Parametersmentioning
confidence: 99%